The Effect of Leadership toward Employees’ Job Satisfaction in Quality Control Division of PT X Padalaran - Listianti, Yulia; Hamali, Arif Yusuf (Bina Nusantara University, 2015)
This research was conducted at Quality Control Division of PT X Padalarang, aimed to determine correlation leadership and job satisfaction, and also to analyze the effect of leadership on job satisfaction at Quality Control Division of PT X Padalarang. Respondents of this research are 52 people selected with simple random sampling technique. The method used is descriptive and associative, which tests the connection using the Spearman rank correlation analysis, and also done to determine the accuracy of measurement using by the validity and reliability test. Results of the validity and reliability test of variables X and Y are valid and reliable. Calculations were performed using SPSS software ver. 19. The result of this study showed that leadership is in the category of good and job satisfaction is in the category of good. Results showed the correlation of leadership with job satisfaction at Quality Control Division of PT X Padalarang with correlation coefficient = 0,679. Based on the criteria champion, this relationship is in the criteria of strong relationship. Results of this calculation showed the coefficient of determination = 46, 10%. It showed that the hypothesis is proved, that there is an influence of leadership to job satisfaction at Quality Control Division of PT X Padalarang.